2014
DOI: 10.1007/s00232-014-9746-9
|View full text |Cite
|
Sign up to set email alerts
|

Salinity-Induced Noise in Membrane Potential of Characeae Chara australis: Effect of Exogenous Melatonin

Abstract: Salt sensitive Characeae Chara australis responds to 50 mM NaCl by a prompt appearance of noise in the trans-membrane potential difference (PD). The noise diminishes with time in saline and PD depolarization, leading to altered current-voltage characteristics that could be modeled with H(+)/OH(-) channels. Beilby and Al Khazaaly (JMB 230:21-34, 2009) suggested that the noise might arise from cooperative transient opening of H(+)/OH(-) channels. Presoaking cells in 10 μM melatonin over 24 h abolished the noise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…To date ROS have been implicated in a multitude of physiological responses such as pathogen attack, herbivory and wounding, and UV exposure as well as playing a role in seed dormancy, and plant growth and development [147][148][149][150][151][152] . In these responses, ROS interact with phytohormone networks and other signaling cascades including calcium, protein phosphorylation and nitric oxide cascades, as well as modifying transcriptional regulation 147,148,153,154 Additionally, work in an ancestral relative of land plant, Chara australis, has found a direct interaction between MEL application and reduced production of ROS species at the cellular level by using fluorescent probes and examining trans-membrane potential differences; these findings have suggested that the natural circadian rhythms of these compounds produced in Chara species may help to regulate ROS levels 124,155 .…”
Section: Melatonin and 5ht In Flowering Reproduction And Chronoregulmentioning
confidence: 97%
“…To date ROS have been implicated in a multitude of physiological responses such as pathogen attack, herbivory and wounding, and UV exposure as well as playing a role in seed dormancy, and plant growth and development [147][148][149][150][151][152] . In these responses, ROS interact with phytohormone networks and other signaling cascades including calcium, protein phosphorylation and nitric oxide cascades, as well as modifying transcriptional regulation 147,148,153,154 Additionally, work in an ancestral relative of land plant, Chara australis, has found a direct interaction between MEL application and reduced production of ROS species at the cellular level by using fluorescent probes and examining trans-membrane potential differences; these findings have suggested that the natural circadian rhythms of these compounds produced in Chara species may help to regulate ROS levels 124,155 .…”
Section: Melatonin and 5ht In Flowering Reproduction And Chronoregulmentioning
confidence: 97%
“…(A) Transition from Sorbitol APW (red) to 50 mM NaCl saline APW (blue) resulted in depolarization and noisy membrane PD. There was no AP, but the resting PD measurement was disrupted by medium change and exhibited spikes between 6800 and 6900 s. (B) Using the same trace on expanded time scale, the higher frequency noise was isolated by subtracting the running average (fitted with n = 100): noise in sorbitol APW (red) and saline-induced noise (blue) that started promptly after ∼50 s of the medium change (data from Beilby et al, 2014). (C) Spontaneous and repetitive APs after ∼80 min of Saline APW (Shepherd et al, 2008).…”
Section: Pathology Of Salt Stress: Salt Sensitive Characeaementioning
confidence: 99%
“…In the animal kingdom, the voltage-gated H + channels in the brain microglia are activated by H 2 O 2 (Wu, 2014). Beilby et al (2014) were able to inhibit or postpone the saline-induced noise by presoaking the Chara cells in strong antioxidant melatonin prior to saline stress. Therefore, H + /OH - channels may be activated by an oxidative burst upon exposure to saline.…”
Section: Pathology Of Salt Stress: Salt Sensitive Characeaementioning
confidence: 99%
See 1 more Smart Citation
“…While there is always some noise in the membrane PD, the degree of "noisiness" was quantified by fitting a running average (n set between 50 and 200), which was then subtracted (Fig. 13.5b, Beilby et al 2014). The classical Fourier analysis identified this increased noise as "red" noise.…”
Section: Saline Stress: H + Pump H + /Oh − Channel Inwardmentioning
confidence: 99%